2021
DOI: 10.1016/j.trip.2021.100495
|View full text |Cite
|
Sign up to set email alerts
|

How will vehicle automation and electrification affect the automotive maintenance, repair sector?

Abstract: Highlights Electrification and automation will affect vehicles maintenance and repair (M&R). Drivers influencing M&R demand provides indications on possible future effects. Less moving parts and regenerative braking systems reduce Battery Electric vehicles’ M&R. Hardware and software and rise in VKT influence autonomous vehicles M&R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…In some cases, such as for maintenance and repair, authors differ not only on the magnitude but even the direction of the change. A similar 2021 European Union study on maintenance and repair also presented a set of studies with large variation in estimates, although the authors concluded based on three selected studies that the trend is towards a decrease in demand [11].…”
Section: How Will Evs Change Vehicle Services?mentioning
confidence: 99%
“…In some cases, such as for maintenance and repair, authors differ not only on the magnitude but even the direction of the change. A similar 2021 European Union study on maintenance and repair also presented a set of studies with large variation in estimates, although the authors concluded based on three selected studies that the trend is towards a decrease in demand [11].…”
Section: How Will Evs Change Vehicle Services?mentioning
confidence: 99%
“…Incorporation of autonomous vehicles into the transport system to increase efficiency and reduce human error-related accidents. [33,[35][36][37][38]…”
Section: Automationmentioning
confidence: 99%
“…Automation, particularly the integration of autonomous vehicles, is expected to ease congestion [35], decrease emissions and fuel consumption [36], and reduce accidents, as these vehicles are designed to minimise human error [37]. Significant investments in infrastructure are required to support this transition [38], but the promise of longterm savings in operational costs due to reduced maintenance and fuel expenses is a key factor [33].…”
Section: Transport Techniques and Technologymentioning
confidence: 99%
“…Similarly, passengers experiencing a ride with an automated shuttle would often use an emergency button inside the vehicle, just to see how the vehicle would react ( Nordhoff et al, 2020 ). Therefore, safety and security should be clearly and transparently ensured, required by regulation ( Fagnant and Kockelman, 2015 ) and supported by insurance schemes ( Baumann et al, 2019 , Grosso et al, 2021a ).…”
Section: Related Workmentioning
confidence: 99%